2021
DOI: 10.1016/j.tmaid.2021.102169
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 infection presented as Guillain-Barre Syndrome: Report of two new cases and review of 116 reported cases and case series

Abstract: Background /Aims: Corona virus disease 2019 (COVID 19) is a pandemic infectious disease of 2020, which often presents with respiratory and gastrointestinal symptoms. The behavior of the virus and its full clinical picture has not been fully studied yet. Many case reports and case series have been running in order to elaborate different presentations and associations. Pulmonary and gastrointestinal features of COVID-19 infection are well outlined; however, neurological manifestations are less defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 112 publications
1
10
0
Order By: Relevance
“…In summary, we agree with Elzouki et al that physicians should consider the co-existence of COVID-19 infection and SC2aG when encountering a GBS patient during the current COVID-19 pandemic and that the suspicion of SC2aG warrants SARS-CoV-2 testing, isolation precautions, and specific treatment for COVID-19 [ 1 ].…”
supporting
confidence: 86%
See 1 more Smart Citation
“…In summary, we agree with Elzouki et al that physicians should consider the co-existence of COVID-19 infection and SC2aG when encountering a GBS patient during the current COVID-19 pandemic and that the suspicion of SC2aG warrants SARS-CoV-2 testing, isolation precautions, and specific treatment for COVID-19 [ 1 ].…”
supporting
confidence: 86%
“…We read with interest the article by Elzouki et al who reviewed 116 cases of SARS-CoV-2 associated Guillain-Barre syndrome (SC2aG) from the literature and reported on two patients with SC2aG in whom Guillain Barre syndrome (GBS) was deemed to have been caused by a para-infectious mechanism rather than post-infectiously [ 1 ].…”
mentioning
confidence: 99%
“…30% of cases resulted in poor outcomes and 6% in deaths. Most patients (75%) received intravenous immunoglobulin (IVIG), 8.5% received plasmapheresis, and 6.8% received some combination of both treatment modalities [92]. Another study found that 23.8% of patients were admitted to the hospital for COVID-19 and either developed GBS during hospitalization or were discharged and later readmitted due to neurologic symptoms.…”
Section: Polyneuropathy Myopathy and Neuromuscular Diseasementioning
confidence: 99%
“…Acute inflammatory demyelinating polyradiculopathy (AIDP), a motor and sensory demyelinating disorder, is the most common subtype of GBS observed in patients with COVID-19. Other subtypes, however, including rare variants such as Miller-Fisher syndrome, have also been observed [92].…”
Section: Polyneuropathy Myopathy and Neuromuscular Diseasementioning
confidence: 99%
“…Since the onset of the Covid-19 pandemic, there have been reports of the possible link between GBS and the GBS occurs with an approximate incidence of 0.16-3 cases per 100,000 annually in the general population; however, an accurate estimation of the incidence of GBS in Covid-19 patients is unknown, as a potential association remains uncertain. After a thorough literature review, found a substantial number of reported cases and case series of Covid-19 infection presented with GBS [8,9]. When compared to the same period of the previous year, we noticed that the cases of acute polyneuropathy have increased three times.…”
Section: Discussionmentioning
confidence: 77%